Instructional decision making in reading in the content areas - Ibanez, Razerly D. (Education quarterly.)
This study investigated instructional decisions of content area teachers in the intermediate level as reflected in their written lesson plans and actual classroom practice. It probed the teaching strategies used and the reasons teachers ascribed to strategy use. Belief themes were generated from teachers? responses obtained from two sets of contextualized interviews using written lesson plans and video vignettes of content area classes as contexts for interview discussions. Findings revealed that content area teachers? instructional decisions in lesson planning are influenced by certain beliefs, namely, belief in matching instruction with students? needs and experiences, belief in guiding students to master content, belief in building and sustaining interest, and belief in paving the way for self-expression. Additionally, two other beliefs influenced content area teachers? instructional decisions in the classroom, namely, a belief in guiding students to learn and a belief in promoting self-expression. The study noted that content area teachers prioritize student motivation and mastery of content in their teaching over the more important concerns of scaffolding students? comprehension.